Linking livelihoods and conservation: a conceptual framework and scale for assessing the integration of human needs and biodiversity - Salafsky, N.; Wollenberg, Eva Karoline (2000)
Although there has been increasing interest in trying to link the livelihoods of people living near natural resources, there has been little attempt to systematically assess or measure this linkage. A conceptual framework for defining the linkage between livelihood activities and conservation is developed and then a scale to assess the strength of linkage across five dimensions: species, habitat, spatial, temporal and conservation association. Evaluating 39 project sites in the Biodiversity Conservation Network tests the framework and scale. Finally, the relevance of linkage to designing appropriate conservation strategies is discussed.